Rheology of Malaysian Tualang honey - Abd. Rahim, Nour El Huda; Mohamed, Farahidah; Ku Zaifah, Norsidah; Zulkifly, Ahmad Hafiz (2011)
KEYWORDS: INTRODUCTION: Malaysian Tualang Honey is a pure honey from combs of Asian honey bees (Apis dorsata) which build their hives high up in the Tualang tree (Koompassia excelsa). The objective of this work was to study the rheological properties of the T ualang honey and the data obtained will be optimized in the development of pharmaceutical products. MATERIALS AND METHOD: There were two types of Tualang honey tested. Pure Tualang honey and oven dried Tualang honey. The oven dried honey was filtered, dehumidified and oven dried at 40ºC by FAMA to reduce the water content less than 20%. Tualang honey was investigated for its rheological properties and evaluated at different temperatures (25°C, 37°C and 40°C). The effect of temperatures on rheological properties needs to be documented because of a wide range of temperatures encountered during processing and storage of pharmaceutical products. RESULTS AND DISCUSSION: The curves constructed showed the shear stress was directly proportionate to the shear rate. In a plot of shear rate against shear stress, both types of Tualang honey produced linearity with straight line passed through origin in all temperatures. The viscosity remains constant throughout the range of shear rate in the rheogram of viscosity against shear rate. These profiles were coherent with behaviour of a simple fluid which is Newtonian fluid. The lowest temperature of Tualang honey had the highest shear stress and viscosity. CONCLUSION: These results suggested that Malaysian Tualang honey is a Newtonian fluid. Eventhough the viscosity decreases with increased temperature but the fluid behaviour was not impaired by reduction in water content. The Newtonian behavior of Tualang honey and its effect on the temperatures are expected to facilitate the process of Tualang honey into pharmaceutical products.